Bunch length compression manipulations - K. M. Fung; M. Ball; C. M. Chu; B. Hamilton; S. Y. Lee; K. Y. Ng (Physical Review Special Topics. Accelerators and Beams, 2000)
Bunch length compression of a single proton bunch is studied by manipulations of the rf voltage and phase. Analytical expressions for the compression ratio, defined as the ratio of the initial to the final bunch lengths, are derived for a linear model. Results obtained from numerical simulations are compared with experimental results. The ultimate maximum compression ratios are found to be sqrt[2]/sqrt[3] σ_{φ,i} for the phase shift method and sqrt[8]/sqrt[3π] σ_{φ,i} for the voltage manipulation method, where σ_{φ,i} is the rms rf-phase spread of the initial beam bunch at the maximum rf voltage. Effects of space charge force are also studied.